2023
DOI: 10.1108/ijis-08-2022-0165
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic rewards for employee creativity? The role of perceived organisational support, work engagement and intrinsic motivation

Hazem Aldabbas,
Ashly Pinnington,
Abdelmounaim Lahrech
et al.

Abstract: Purpose This study aims to investigate the relationship between extrinsic rewards and employee creativity through the intervening mechanism of perceived organisational support (POS) and work engagement. The moderating role of intrinsic motivation on the relationship between work engagement and employee creativity is also examined. Design/methodology/approach The authors report the results of a survey completed by 372 respondents employed in the United Arab Emirates. Structural equation modelling was applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…Employee creativity fundamentally and cumulatively contributes to the improvement of company performance (Madjar et al, 2002;Rumanti, Rizana, & Achmad, 2023). Foregoing research has confirmed the relationship between creativity and finding meaning in one's work, with this leading to performance improvement (Akgunduz, Alkan, & Gök, 2018;Al-Hawari, Quratulain, & Melhem, 2021;Khan & Abbas, 2022).…”
Section: H4mentioning
confidence: 91%
See 3 more Smart Citations
“…Employee creativity fundamentally and cumulatively contributes to the improvement of company performance (Madjar et al, 2002;Rumanti, Rizana, & Achmad, 2023). Foregoing research has confirmed the relationship between creativity and finding meaning in one's work, with this leading to performance improvement (Akgunduz, Alkan, & Gök, 2018;Al-Hawari, Quratulain, & Melhem, 2021;Khan & Abbas, 2022).…”
Section: H4mentioning
confidence: 91%
“…Pair dimensions and eight indicators, as developed by Akgunduz et al (2018) and Rhoades and Eisenberger (2002), were used to measure perceived organizational support. To measure employee engagement, the current study utilized three dimensions and 13 indicators based on instruments developed by Schaufeli et al (2002) and Aldabbas et al (2023). Furthermore, to measure employee creativity, this research applied two dimensions and 13 indicators, adopted from studies by Zhou and George (2001) and Elidemir et al (2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations